High and low level of flexibility is not a predictor for speed and explosiveness performance in professional soccer players - Hadjicharalambous, M.; Christou, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Flexibility has been considered to be an essential element of daily training programs in several sports (Magnusson and Restroom, 2006). It was suggested that increasing flexibility may contribute in improving exercise performance and preventing from injuries (Smith, 1994). However, no studies so far evaluated whether poor or good flexibility may influence fitness parameters in elite soccer-players. The purpose of the present study was to examine the effect of lower back and hamstrings` flexibility on several fitness parameters in elite soccer players. Methods: Ninety four professional soccer players were initially evaluated, but, only seventy one (mean+/-SD) met the cut-off criteria and were included into the statistical analysis. These 71 players were separated into two groups based on their sit-and-reach flexibility score. The players whose reach score was less than 22cm developed the low-flexibility (low-Flex) group (n=28); and those whose reach score was above 28cm were included into the high-flexibility (high-Flex) group (n=43). A comparison between the two groups was performed following a series of anthropometric and fitness parameters evaluations. Results: Sit-and-reach flexibility was significantly higher (p=0.0001) in high-Flex (31.4+/-3) compared with the low-Flex (17.4+/-6) group. No significant differences were observed on age, height, weight, body fat%, on several countermovement jumps and on 10 and 30 meters maximum speeds (p>0.05). Peak oxygen consumption (VO2peak) was significantly higher (p=0.004) in the high-Flex (VO2peak: 56.03+/-3.2 ml/kg/min) compared with the low-Flex (VO2peak: 53.87+/-3.1 ml/kg/min) group. No statistical significant correlations were observed between flexibility score and any other depended variable measured in both groups. Discussion: In conclusion, high level of sit-and-reach flexibility may contribute in enhancing aerobic capacity and/or low levels of sit-and-reach flexibility may diminish running economy in professional soccer players; but the exact mechanism responsible for this result still needs to be determined. However, neither high nor low levels of sit-and-reach flexibility should be considered as a limiting factor in speed and explosiveness performance but poor lower back and hamstrings` flexibility might be a limiting factor in achieving high endurance performance in soccer.